Ocena powszechności certyfikowanych systemów zarządzania jakością na Dolnym Śląsku - Rogala, Piotr; Brzozowski, Tomasz; Skowron, Paweł (Commonness of certified quality management systems in Lower Silesia Regio, 2005)
The number of organizations, which have implemented and certificated a quality management system is still increasing. There are about 5000 ISO 9001 certificates in Poland. This paper presents a classification of regions in Poland using two indicators - number of certificates considering the number of 100000 inhabitants and 10000 enterprises. In this way we identified both regions with the largest number of ISO 9001 certificates and those, where certification is less popular.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 173-181